Rate and predictors of progression in elite and viremic HIV-1 controllers. (15th May 2016) - Leon, Agathe; Perez, Ignacio; Ruiz-Mateos, Ezequiel; Benito, Jose Miguel; Leal, Manuel; Lopez-Galindez, Cecilio; Rallon, Norma; Alcami, Jose; Lopez-Aldeguer, Jose; Viciana, Pompeyo; Rodriguez, Carmen; Grau, Eulalia; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: The proportion of HIV controllers developing virologic, immunological or clinical progression and the baseline predictors of these outcomes have not been assessed in large cohorts. Methods: A multicenter cohort of HIV controllers was followed from baseline (the first of the three HIV-1 RNA levels < 50 in elite controller or from 50 to 2000 copies/ml in viremic controllers) up to August 2011, to the development of a progression event (loss of viral load control, CD4 + decline, AIDS or death) or to the censoring date (lost to follow-up or initiation of antiretroviral therapy). Predictive models of progression at baseline and a risk score for the combined HIV-1 progression end point were calculated. Results: Four hundred and seventy-five HIV-1 controllers of whom 204 (42.9%) were elite controller with 2972 person-years of follow-up were identified. One hundred and forty-one (29.7%) patients lost viral load control. CD4 + cell count declined in 229 (48.2%) patients. Thirteen patients developed an AIDS event and four died. Two hundred and eighty-seven (60.4%) developed a combined HIV-1 progression. Baseline predictors for the progression end points and for elite and viremic controller patients were very similar: risk for HIV-1 acquisition, baseline calendar year, CD4 + nadir, viral load before baseline and hepatitis C virus coinfection. The probability of a combined HIV-1 progression at 5 years was 70% for elite controllers with the highest score compared with 13% for those with the lowest. Conclusion: HIV-1 disease progression in elite and viremic controllers is frequent. We propose a baseline clinical score to easily classify these patients according to risk of progression. This score could be instrumental for taking clinical decisions and performing pathogenic studies.